Feline panleukopaenia virus in captive non-domestic felids in South Africa - Lane, Emily P. (Onderstepoort J Vet Res, 2016)
An outbreak of feline panleukopaenia virus (FPLV) infection was diagnosed by pathology, electron microscopy and polymerase chain reaction (PCR) in vaccinated captive-bred subadult cheetahs in South Africa. Subsequent to this disease outbreak, 12 cases of FPLV diagnosed on histology were confirmed by PCR in captive African black-footed cat, caracal, cheetah, lion, ocelot and serval. Phylogenetic analyses of the viral capsid protein gene on PCR-positive samples, vaccine and National Center for Biotechnology Information (NCBI) reference strains identified a previously unknown strain of FPLV, present since at least 2006, that differs from both the inactivated and the modified live vaccine strains. A previously described South African strain from domestic cats and cheetahs was identified in a serval. Surveys of FPLV strains in South African felids are needed to determine the geographical and host species distribution of this virus. Since non-domestic species may be reservoirs of parvoviruses, and since these viruses readily change host specificity, the risks of FPLV transmission between captive-bred and free-ranging carnivores and domestic cats and dogs warrant further research.